2019
DOI: 10.13057/biodiv/d201140
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon degradation by bacteria from rhizospheres of Imperata cylindrica at oil mining site in Wonocolo, Bojonegoro, Indonesia

Abstract: Abstract. Sari MA, Retnaningrum E. 2019. Hydrocarbon degradation by bacteria from rhizospheres of Imperata cylindrica at oil mining site in Wonocolo, Bojonegoro, Indonesia. Biodiversitas 20: 3422-3429. High oil mining activities cause environmental pollution at the oil mining site. Petroleum spills and waste to the river flow cause blackish discoloration along the riverbank and also some types of plants die. The utilization of rhizospheric bacteria (rhizobacteria) as a bioremediation agent is considered as app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Several studies on biological agents for reducing oil pollution have been reported, including Staphylococcus pasteuri, Staphylococcus epidermidis, Pseudomonas aeruginosa, Bacillus subtilis, Bacillus pumilus (Kanmani et al 2015;Lauprasert et al 2017;Saranya et al 2019). Other studies on the ability of the biological agents to degrade hydrocarbon pollutants have also been reported, including Pseudomonas aeruginosa, Pseudomonas sp, Bacillus sp (Retnaningrum and Wilopo 2017;Xia et al 2019;Sari and Retnaningrum 2019;Benget and Retnaningrum 2020). Bacterial isolates such as Pseudomonas sp, Rhodococcus sp, and Comamonas sp have been investigated for their potential in reducing plastics pollution (Urbanek et al 2018;Danso et al 2019), while Pseudomonas fluorescens can reduce pollutant pesticides (Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on biological agents for reducing oil pollution have been reported, including Staphylococcus pasteuri, Staphylococcus epidermidis, Pseudomonas aeruginosa, Bacillus subtilis, Bacillus pumilus (Kanmani et al 2015;Lauprasert et al 2017;Saranya et al 2019). Other studies on the ability of the biological agents to degrade hydrocarbon pollutants have also been reported, including Pseudomonas aeruginosa, Pseudomonas sp, Bacillus sp (Retnaningrum and Wilopo 2017;Xia et al 2019;Sari and Retnaningrum 2019;Benget and Retnaningrum 2020). Bacterial isolates such as Pseudomonas sp, Rhodococcus sp, and Comamonas sp have been investigated for their potential in reducing plastics pollution (Urbanek et al 2018;Danso et al 2019), while Pseudomonas fluorescens can reduce pollutant pesticides (Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%